2017
DOI: 10.1159/000472717
|View full text |Cite
|
Sign up to set email alerts
|

68Gallium DOTANOC-PET Imaging in Lung Carcinoids: Impact on Patients' Management

Abstract: Background:68Gallium DOTA-PET imaging is preferable to standard somatostatin receptor scintigraphy where available; however, its role in the management of lung carcinoid tumours (LC) remains unclear. Methods: All consecutive patients with histologically confirmed LC from two ENETS Centres of Excellence were identified retrospectively. The primary objective was to assess the impact of 68Ga-DOTANOC-PET on clinical management in patients with LC. Results: Of 166 patients screened, 46 were el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Indeed, expression of somatostatin receptors has been demonstrated in lung NET [37,38]. On this basis, recent series, using 68 Ga-DOTANOC-PET and DOTATATE-PET, showed promising results in patients with lung NET [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, expression of somatostatin receptors has been demonstrated in lung NET [37,38]. On this basis, recent series, using 68 Ga-DOTANOC-PET and DOTATATE-PET, showed promising results in patients with lung NET [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Whilst 68 Ga-DOTA somatostatin analogue PET/CT generally reveals additional metastases compared to conventional imaging (e.g., CT/MRI) in well-differentiated NET [35], especially of lymph nodes, bone, and peritoneum, there are no dedicated studies yet to determine the performance of SRI in the pre- or postoperative setting of early-stage PC, namely for the detection of mediastinal node metastases. A few studies dedicated to advanced PC have provided first evidence that the rate of new sites discovered by SRI is above 10%, supporting its routine use [36]. 18 F-FDG PET/CT is currently recommended in aggressive PC, but due to its historical role in lung cancer 18 F-FDG PET/CT is frequently performed first [37].…”
Section: Classification and Diagnosticsmentioning
confidence: 99%
“…In the last decade, several clinical studies have compared the diagnostic role of 68 Ga-DOTA-PET to somatostatin receptor scintigraphy (Octreoscan ® ) in patients diagnosed with NETs. These studies have confirmed an increased sensitivity and image quality, together with an increased capacity to detect additional lesions and alter management in favour of 68 Ga-DOTA-PET [72,73,74,75,76,77,78].…”
Section: How? Presurgical Staging and Follow-up Toolsmentioning
confidence: 83%